I will learn better later - procrastination and perfectionism in students included in CBT group therapy - Novak, Miranda (Array, 2008)
I will learn better later Procrastination and perfectionism in students included in CBT group therapy Novak, M., Jurin, T. Procrastination is not unknown in student population in general. Nevertheless, excessive procrastination leads to academic failure and consequentially to emotional disturbances (Beck et al, 2000). Procrastinators place unrealistic demands on themselves (Flett et al, 1992) and have excessive fear of failure which is the same for some aspects of perfectionism (Solomon and Rothblum, 1984 ; Frost et al, 1990). The aim of the research was to examine the relation in procrastination and perfectionism behaviour in college student population which came to seek help in Student Counselling Centres regarding learning difficulties. Also, our goal was the qualitative analysis of specific characteristics of learning difficulties among high procrastinators. Participants of the study were the students included in CBT group therapy for learning difficulties in Student Counselling Centres. Participants were voluntary and self-administered, coming to Counselling Centre because of problems with learning, concentration, motivation, failure on exams, fear of exams and professors or other problems related to college. A sample of 86 college students completed the Frost multidimensional perfectionism scale (Frost et al, 1990), Procrastination assessment scale and were asked about specific learning disabilities. The main findings show the positive correlation between 3 perfectionism factors (doubts about actions, parental expectations and parental criticism) and procrastination. Also, the procrastination is in negative connection with other two perfectionism factors (organisation and personal standards). No significant correlation was found between procrastination and total perfectionism scores. The present study clarifies the association between procrastination and multidimensional perfectionism. It seems that college students which received more parental criticism, who perceive high parental expectations and doubt their actions, are more likely to procrastinate more and have more difficulties during college time. Qualitative analysis will be further discussed.